Evaluation of the cytotoxic activity of extracts from medicinal plants used for the treatment of malaria in Kagera and Lindi regions, Tanzania - Ramadhani S. O. Nondo, Mainen J. Moshi, Paul Erasto, Denis Zofou , Abdel J. Njouendou, Samuel Wanji, Moses N. Ngemenya, Abdul W Kidukuli, Pax J. Masimba, Vincent P.K. Titanji (Journal of Applied Pharmaceutical Science, 2015)
A number of medicinal plants used for treatment of malaria in Tanzania have been documented, but information on their safety and efficacy is still based on traditional knowledge accumulated over years and not on pre-clinical and clinical evaluation. The present study aimed to assess the cytotoxic activity of extracts of selected plant species used for treatment of malaria in Tanzania. Ethanol extracts were evaluated for cytoxicity by using MTT assay on LLC-MK2 cells and by brine shrimp lethality assay. Forty five (93.75%) out of 48 crude extracts assessed using LLC-MK2 cells were non-cytotoxic while three extracts (6.25%) were cytotoxic with CC50
Keywords: Toxicity, medicinal plants, malaria, LLC-MK2 cells, brine shrimps assay, Tanzania.